The case of plantations under green resources Ltd and SAOHILL forest plantations in Mufindi District - Elia, Hosea (Mzumbe university, 2024)
A dissertation submitted as a partial fulfillment of the requirements for the award of the degree of Master of Business Administration (MBA) of Mzumbe university